Med sovraštvom in tišino - Ferbežar, Nika (Družboslovne razprave, 2023)
We examine the experiences of LGBT+ people in education, which international research shows is characterised by a lack of sensitivity to gender and sexual minorities. We conducted a qualitative study involving 27 individual interviews with LGBT+ persons who attend or have attended primary, secondary and/or tertiary education in Slovenia. The analysis revealed that the typical experience entails a combination of hate and invisibility. The data show the all-encompassing influence of prejudice, which people mention in various situations. Less common are descriptions of protective factors, which are generally limited to peer support and the commitment of individual staff members. The lack of systemic solutions is a challenge that must be addressed in the future by developing opportunities for inclusive formal and hidden curricula and staff training.
Keywords: Biseksualnost; dejavniki tveganja; education system; experiences; Homoseksualne osebe; izkušnje; LGBT+ students; LGBT+ učenci; protective factors; risk factors; Transseksualnost; varovalni dejavniki; vzgojno-izobraževalni sistem